Substitute y = 2x - 15 to the second equation:
4x + 3(2x - 15) = -5 use distributive property
4x + (3)(2x) + (3)(-15) = -5
4x + 6x - 45 = -5 add 45 to both sides
10x = 40 divide both sides by 10
x = 4
Substitute the value of x to the equation y = 2x - 15:
y = 2(4) - 15 = 8 - 15 = -7
<h3>Answer: (4, -7)</h3>
Answer:
x = 7
Step-by-step explanation:
5x + 9 = 6x + 2
5x - 6x = 2 - 9
-x = -7
x = 7
probe:
5*7 + 9 = 6*7 + 2
35 + 9 = 42 + 2 = 44
Answer:
y=-14acfr+5x
Step-by-step explanation:
hope it helps
Answer:
7 3/4+(-1/2)
Step-by-step explanation: